The Drama on Provincial Accented Speech - Malon, Jake (International Journal of Language and Literary Studies, 2022)
This phenomenological study looked into the lived experiences of fourth-year students exposed to the drama of provincial accented speech. Colaizzi's descriptive approach was used in the study with the purposively chosen key informants with various tools to cross-check their responses. Results showed biases on an accent because the informants thought inferiority of their accent, harassment on accented speech for they experience overt linguistic racism, probable accent discrimination, and accent intelligibility were some of the issues the students encountered. However, there were also feats to consider in using provincial accented speech to fellow second language (L2) English speakers. These were the accent sapiency and accented speech ego and pride. Based on the study’s findings, the English second language teachers and professionals are encouraged to address these identified dramas, for they have a valuable role, provided they possess the knowledge and attitudes needed to foster acceptance of linguistic diversity.